Dampak Pascapenggunaan Game Online Terhadap Kepuasan Hidup: Studi pada Komunitas Esport UMJ - Elvira Salsabila; Moh. Amin Tohari (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study use a descriptive qualitative approach to examine the life satisfaction of members of the UMJ Esport community after engaging in online gaming. Informants were selected through purposive and snowball sampling techniques. Life satisfaction was analyzed through both external factors, such as economic security, social support, and social equality, and internal factors, including positive relationships and self-regulation. This study using the Uses and Gratifications theory as the analytical framework. The findings indicate that online gaming contributes to enhanced social and emotional well-being, particularly by fostering social connections and reducing stress, although the impact varies among individuals.